Seleção e preferência de microhábitats por larvas de peixes migradores. - Taguti, Tátia Leika (2011)
The sub-basin of Ivinhema River with its different environments, present high biodiversity, habitat heterogeneity and consequently, food and shelter. This environment, free of impoundment, is fundamental to the reproduction of migratory fish species, which have suffered reduction in its population due to human disturbances. Thus, this study aimed to understand the habitat selection and reproductive dynamics of migratory species that use the Ivinheima River and its catchment area as spawning and growth. Therefore, samples were taken along nychthemeral cycles in six consecutive reproductive periods (October-March 2002-2008). The Larvae were collected at the surface and bottom of water column, with plankton nets with a conical-cylindrical mesh of 0.5 mm and flow meter attached to the mouth. Concurrently to the ichthyoplankton samples, water samples were collected for determination of some environmental variables. In the laboratory, samples were screened and the migratory larvae identified and separated by the degree of flexion of notochord. Differences in spatial variations of the larvae were evaluated by Analysis of Variance, Principal Component Analysis, Spearman Correlations and mantel test. The characterization of diet and feeding activity of most abundant species were performed. The diet analysis was performed using the methods of frequency of occurrence and numerical frequency. 2908 larvae were captured of migratory fish, consisting of eight species, among which, P. Corruscans is the most abundant. It was found that the reproduction of migratory fish occurs mainly during months from November to January, and its density is influenced by abiotic factors, specifically the concentration of dissolved oxygen in the river, temperature and electrical conductivity in the lagoons. The larvae showed a preference for habitats with low flow velocity, since their abundance and feeding activity was higher in these locations. The degree of development is related spatially: the newly hatched larvae more abundant in the river and later stages in the lagoons. Thus, the Ivinheima River, the Finado Raimundo and Patos Lagoons have proved to be essential for the reproductive success of migratory fish species, the River functioning as a real canal for dispersion of larvae and the lagoons as an area for development and growth.